The Impact of Work Life Balance on Job Engagement and Turnover Intention: A Case of Nepalese Insurance Company - Awasthi, Kamala (Nepalese Journal of Management, 2025)
This study examines the impact of work life balance on job engagement and turnover intention. A case of Nepalese insurance company. Job engagement and turnover intention are the dependent variables. The selected independent variables are organizational factor, individual factor, job satisfaction, employees’ time for family, and daily working hour. The primary source of data is used to assess the opinions of respondents regarding organizational factor, individual factor, job satisfaction, employees’ time for family, daily working hour, job engagement, and turnover intention. The study is based on primary data of 127 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of impact of work life balance on job engagement and turnover intention. A case of Nepalese insurance company. The study showed a positive impact of organizational factor on job engagement. It indicates that organizational support lead to better job engagement decision. In contrast, the study showed a negative impact of organizational factor on turnover intention. It indicates that supportive organizational culture leads to lower the turnover intention. Likewise, the study showed a positive impact of individual factor on job engagement. It indicates that better future job opportunities attract employee towards job engagement. However, the study showed a negative impact of individual factor on turnover intention. It indicates that growth opportunities for individual within the organization leads to decrease in turnover intention. Further, the study revealed a positive impact of job satisfaction on job engagement. It indicates that higher the job satisfaction, higher would be the job engagement. However, the study showed a negative impact of job satisfaction on turnover intention. It indicates that higher the job satisfaction, lower would be the turnover intention. In addition, the study showed a positive impact of employee’s time for family on job engagement. It indicates that sufficient time of employee’s for family leads to increase in job engagement. In contrast, the study showed a negative impact of employees’ time for family on turnover intention. It indicates that sufficient time of employee’s for family leads to decrease in turnover intention. Further, the study showed a positive impact of daily working hour on job engagement. It indicates that fixed working hour leads to increase in job engagement. However, the study showed a negative impact of daily working hour on turnover intention. It indicates that fixed daily working hour leads to decrease in turnover intention.